The Critical Role of Social Interaction, Social Trust, and Social Aid in Marketing Subang Regency - Tania Julianti; Yadi Ernawadi (LP2M IAIN Palopo, 2026)
This study aims to examine the influence of social environment quality on resident commitment through place attachment and resident satisfaction of Subang Regency residents. This study used a survey method as a research method by determining a sample of 146 respondents. Data analysis was conducted using structural equation modeling (SEM) techniques with the SmartPLS version 3.0 tool. The results of the study indicate that social interaction and social trust influence resident commitment through place attachment. Then, social interaction, social trust, and social aid influence resident commitment through resident satisfaction. The novelty in this study is the addition of social aid which is hypothesized to influence resident commitment and adding resident satisfaction which is hypothesized to influence resident commitment. The researcher hopes that the results of this study can provide benefits for further researchers and the Subang Regency government regarding the design of strategies relevant to improving the quality of these attributes.